Diversity in the incidence and spectrum of organic acidemias, fatty acid oxidation disorders, and amino acid disorders in Asian countries: Selective screening vs. expanded newborn screening - Shibata, Naoaki; Hasegawa, Yuki; Yamada, Kenji; Kobayashi, Hironori; Purevsuren, Jamiyan; Yang, Yanling; Dung, Vu Chi; Khanh, Nguyen Ngoc; Verma, Ishwar C.; Bijarnia-Mahay, Sunita; Lee, Dong Hwan; Niu, Dau-Ming; et al. (Molecular genetics and metabolism reports, 2018)
Background - Expanded newborn screening (ENBS) utilizing tandem mass spectrometry (MS/MS) for inborn metabolic diseases (IMDs), such as organic acidemias (OAs), fatty acid oxidation disorders, (FAODs), and amino acid disorders (AAs), is increasingly popular but has not yet been introduced in many Asian countries. This study aimed to determine the incidence rates of OAs, FAODs, and AAs in Asian countries and Germany using selective screening and ENBS records. - Materials and methods - Selective screening for IMDs using gas chromatography-mass spectrometry and MS/MS was performed among patients suspected to be afflicted in Asian countries (including Japan, Vietnam, China, and India) between 2000 and 2015, and the results from different countries were compared. Similarly, ENBS results from Japan, South Korea, Taiwan, and Germany were compared. Additionally, the results of selective screening and ENBS in Japan were compared. - Results - Among 39,270 patients who underwent selective screening, IMDs were detected in 1170. Methylmalonic acidemia was frequently identified in several countries, including Japan (81/377 diagnosed IMDs), China (94/216 IMDs), and India (72/293 IMDs). In Vietnam, however, β-ketothiolase deficiency was particularly frequent (33/250 IMDs). ENBS yielded differences in overall IMD rates by country: 1:8557 in Japan, 1:7030 in Taiwan, 1:13,205 in South Korea, and 1:2200 in Germany. Frequently discovered diseases included propionic acidemia (PPA) and phenylketonuria (PKU) in Japan, 3-methylcrotonyl-CoA carboxylase deficiency (MCCD) and PKU in Taiwan, MCCD and citrullinemia type I in South Korea, and PKU and medium-chain acyl-CoA dehydrogenase deficiency in Germany. Furthermore, in Japan, selective screening and ENBS yielded respective PPA frequencies of 14.7% and 49.4% among all organic acidemias. - Conclusion - The incidence rates of IMDs vary by country. Moreover, the disease spectra of IMDs detected via selective screening differ from those detected via ENBS.
Gesehen am 01.10.2019